Hierarchically patterned multiphase steels created by localised laser treatments. (September 2022) - Breukelman, H.J.; Santofimia, M.J.; Hidalgo, J.
Graphical abstract: Highlights: fcc/bcc patterned mesostructures are created by solid-state transformations in a Fe-Ni-C steel through the application of local laser heat treatments. The behavior of fcc/bcc mesostructures is controlled by the topology and the martensite strength, which can be tailored through tempering. The proposed approach to create patterned mesostructures opens new strategies in the design of steel and other metal alloys. Abstract: The realisation of sophisticated hierarchically patterned multiphase steels has the potential to enable unprecedented properties in engineering components. The present work explores the controlled creation of patterned multiphase steels in which the patterns are defined by two different crystal structures: face centre cubic or fcc (austenite) and body centre cubic or bcc (martensite). These austenite/martensite mesostructures are generated by solid–solid phase transformations during the application of localised laser heat treatments in a Fe-Ni-C alloy. In particular, four patterned configurations are analysed in this work consisting of one or two horizontal austenite line structures imprinted in a base of as-quenched or tempered martensite. Digital image correlation analysis during tensile testing of the developed materials showed that both the strength of the base martensite and the mesostructure at the gauge have a strong effect on the resulting properties. Clear differences were observed among the configurations in strain partitioning, hardening of the different constituents and failure. The uniform elongation and tensile strength are increased with respect to that of the reference martensite and austenite, respectively. Concepts explored in this work can be extended to more complex patterns and other base microstructures, opening novel strategies to engineer properties in steel and other alloys.